Manajemen Pembelajaran Terintegrasi dalam Model Pembelajaran Blended Learning, Learning Management System - Firman, Muhammad; Berliana, Berliana; Sauri, R.Supyan; Wasliman, Iim (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
The primary objective of this research is to examine the impact of the blended learning model based on the Learning Management System (LMS) on both student learning outcomes and motivation. Within the realm of education, students often encounter various challenges, such as a lack of enthusiasm, boredom, and difficulties in grasping learning materials due to the limited variety in teaching and learning approaches. To address these issues, this study adopts a survey method employing a quantitative approach. The study encompasses all students at STKIP PGRI Sukabumi, with a sample size of 100 students chosen through the Simple Random Sampling technique. Data collection is conducted via a questionnaire distributed through Google Forms. The analysis involves multiple linear regression utilizing the SPSS 23 program, and the findings are as follows: 1. The LMS-based blended learning model demonstrates a significant influence on learning outcomes, as indicated by the t-count value of 6.835, surpassing the t-table value of 1.984. 2. Learning motivation is identified as a significant factor affecting learning outcomes, with a t-count value of 10.216, exceeding the t-table value of 1.984. 3. Both the LMS-based blended learning model and learning motivation collectively exhibit a substantial impact on learning outcomes, evidenced by an F-count value of 59.851, surpassing the F-table value of 3.089. In summary, the study concludes that the integration of the LMS-based blended learning model and enhanced learning motivation plays a pivotal role in advancing student learning outcomes.